2015
DOI: 10.1007/978-3-319-20810-7_24
|View full text |Cite
|
Sign up to set email alerts
|

Inference Leakage Detection for Authorization Policies over RDF Data

Abstract: Abstract. The Semantic Web technologies include entailment regimes that produce new RDF data from existing ones. In the presence of access control, once a user has legitimately received the answer of a query, she/he can derive new data entailed from the answer that should have been forbidden if carried out inside of the RDF store. In this paper, we define a fine-grained authorization model for which it is possible to check in advance whether such a problem will arise. To this end, we provide a static analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Data outsourcing and the inference problem is a research field that researchers have begun to investigate few years ago (Biskup et al, 2011;de Mantaras & Saina, 2004;di Vimercati et al, 2014;Haddad et al, 2014;Sayah et al, 2015;Sellami et al, 2015;Turan et al, 2017Turan et al, , 2018. Inference leakage is recognized as a major barrier to cloud computing and other data outsourcing or Database-As-a-Service arrangements.…”
Section: Inference Control In Cloud Data Integration Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data outsourcing and the inference problem is a research field that researchers have begun to investigate few years ago (Biskup et al, 2011;de Mantaras & Saina, 2004;di Vimercati et al, 2014;Haddad et al, 2014;Sayah et al, 2015;Sellami et al, 2015;Turan et al, 2017Turan et al, , 2018. Inference leakage is recognized as a major barrier to cloud computing and other data outsourcing or Database-As-a-Service arrangements.…”
Section: Inference Control In Cloud Data Integration Systemsmentioning
confidence: 99%
“…Inference control in cloud integration systems has been investigated in the last decade through the work of Haddad et al (2014), Sayah et al (2015), Sellami et al (2015). In such systems, a mediator is defined as a unique entry point to the distributed data sources.…”
Section: Inference Control In Cloud Data Integration Systemsmentioning
confidence: 99%
“…Inference control in data integration systems have been investigated in the last decade through the works in [12,17,18]. In such systems, a mediator is defined as a unique entry point to the distributed data sources.…”
Section: B Inference Control In Data Integration Systemsmentioning
confidence: 99%
“…Complying with source policies means that a prohibited access at the source level should be also prohibited at the global level. [12,17,18] have demonstrated that despite the generation of a global policy at the mediator level that synthesizes and enforces the back-end data sources policies, security breaches still possible via inference channel produced by semantic constraints. The problem is that the designer of the system cannot anticipates the inference channels that arise due to the dependencies that appear at the mediator level.…”
Section: B Inference Control In Data Integration Systemsmentioning
confidence: 99%
See 1 more Smart Citation